Reporting reactive cellular changes on smears among women who undergo cervical cancer screening: results of a cohort study after seven years of follow-up. (September 2017) - Moitry, Marie; Jégu, Jérémie; Averous, Gerlinde; Velten, Michel; Fender, Muriel; Akladios, Cherif; Baldauf, Jean-Jacques
Abstract: Objective: To identify whether women presenting with reactive cellular changes (RCC) on their cervical smear face an increased risk for developing high grade cervical intraepithelial neoplasia (CIN2-3) or cancer as compared with women with an entirely normal smear. Study design: French data from the association in charge of organized cervical cancer screening in Bas-Rhin administrative region were used to establish a cohort of 96, 215 women presenting with a smear classified as entirely normal or with RCC during the year 2001. The Kaplan-Meyer method was used to calculate the probabilities of CIN2-3 and cancer at seven years of follow-up. Univariate and multivariate survival analyses were performed using Cox proportional hazard models. Results: Among the 95, 559 women included in the final analysis, 32.2% presented a smear with RCC. After seven years of follow-up, 441 women developed a CIN2-3 and 35 a cancer. Probability of CIN2-3 was increased in the RCC group as compared with the group of women with a normal smear (0.7% versus 0.5%, p = 0.002). Multivariate analyses showed that, compared with a normal cervical smear, RCC were associated with a significant 37% increased risk of CIN2-3 (HR = 1.37 CI95 [1.13–1.66]). However, the risk of cancer was not significantly increased (HR = 1.11 CI95 [0.55–2.23]). Conclusion: This study showed that, at seven years, women with RCC on their cervical smear face an increased risk of CIN2-3 but no significant increased risk of cancer. The distinction between entirely normal and RCC cervical smears should therefore not lead to specific clinical management.